2022
DOI: 10.1002/jhm.12789
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuation of atorvastatin use in hospital is associated with increased risk of mortality in COVID‐19 patients

Abstract: Background: Statins are a commonly used class of drugs, and reports have suggested that their use may affect COVID-19 disease severity and mortality risk.Objective: The purpose of this analysis was to determine the effect of discontinuation of previous atorvastatin therapy in patients hospitalized for COVID-19 on the risk of mortality and ventilation.Methods: Data from 146,413 hospitalized COVID-19 patients were classified according to statin therapy. Home + in hospital atorvastatin use (continuation of therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Moreover, continuation of ACE inhibitor/ARB outpatient treatment after hospitalization has beneficial effects on COVID-19 outcomes [ 163 ], whereas discontinuing treatment can be harmful [ 164 , 165 , 166 , 167 , 168 ]. Similarly, an increase in COVID-19 mortality has been observed following withdrawal of statin treatment [ 169 , 170 ]. Withdrawal of treatment with these drugs is discussed in greater detail below.…”
Section: Treating the Host Response To Covid-19 With Inexpensive Gene...mentioning
confidence: 99%
“…Moreover, continuation of ACE inhibitor/ARB outpatient treatment after hospitalization has beneficial effects on COVID-19 outcomes [ 163 ], whereas discontinuing treatment can be harmful [ 164 , 165 , 166 , 167 , 168 ]. Similarly, an increase in COVID-19 mortality has been observed following withdrawal of statin treatment [ 169 , 170 ]. Withdrawal of treatment with these drugs is discussed in greater detail below.…”
Section: Treating the Host Response To Covid-19 With Inexpensive Gene...mentioning
confidence: 99%
“…A hospital-based study in the US showed that the odds of mortality decreased by 35% in statin-users who continued to use statins upon hospital admission for COVID-19 compared with those for which the. statin therapy was discontinued 53 . The effect of discontinuation of statin treatment on the risk of COVID-19 in a population needs to be investigated in further detail.…”
Section: Characteristicsmentioning
confidence: 99%
“…Reduction in the risk of death (up to 28% as evaluated in 2.9 million patients [ 24 ]) was found. Discontinuation of previous statin therapy on hospital admission once diagnosed with COVID-19 could therefore result in a worse outcome (OR, 0.65; 95% CI, 0.59–0.72; p < 0.001) [ 27 ]. Benefits were established in COVID-19 patients previously treated and maintained on statin therapy during hospitalization in comparison to patients in whom therapy was withdrawn on admission.…”
Section: Clinical Studies Investigating the Benefits Of Statins In Co...mentioning
confidence: 99%